Personal qualities conditioning the success of a social work specialist - Dvoretskaya, Victoria A. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
The importance of the professional and personal qualities of a social work specialist is considered. Different positions are presented regarding the requirements for professional and personal qualities of a social work specialist. Analysis of the essence of social work shows that a professional specialist in social work should be a holder of ethical and qualification standards regarding relations between people, between people and society, relations in the family, in the labour collective, community and other. The components of readiness for professional activity are identified. The motivational sphere of the future specialist in social work is determined, ensuring the development of spiritual and moral qualities, including the mental, strong-willed and emotional sides of the person. From the standpoint of the activity approach, the necessary skills of a specialist in social work are distinguished: analytical, constructive, performing, taking into account professional and personal qualities. Issues of a person’s career path in the field of social work are being studied.
Keywords: specialists in social work; professional and personal qualities; spiritual and moral qualities; personal characteristics of a specialist in social work; career; career development